2004
DOI: 10.1002/ejic.200300725
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of the Diastereomers Λ‐ and Δ‐[Ru(bpy)2(m‐bpy‐Gly‐L‐His‐L‐Lys)]Cl21H NMR Studies on Their Interactions with the Deoxynucleotide Duplex d[(5′‐CGCGAATTCGCG‐3′)2]

Abstract: The synthesis and characterization of the diastereomeric complexes Λ-and ∆-[Ru(bpy) 2 (m-bpy-GHK)]Cl 2 , (GHK = glycine-L-histidine-L-lysine, m-bpy = 4͉-methyl-2,2͉-bipyridine) as well as their binding properties to the deoxynucleotide duplex d(5Ј-CGCGAATTCGCG-3Ј) 2 studied by means of NMR, ESI-MS and CD spectroscopy, are reported. The ROESY spectrum of Λ-[Ru(bpy) 2 (m-bpy-GHK)]Cl 2 shows intramolecular cross peaks between the bpy H3 or H3Ј protons and the aromatic H2 and H5 of the histidine imidazole ring, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Inspection of Figure 9a reveals that the degeneracy in chemical shifts due to the C 2V symmetry of ligand B (dppz) remains unchanged in rac–1a (except for a 0.04 ppm difference between positions 2 and 11), which suggests the very similar anisotropic effect of the substituted phenanthrolines in this arrangement. Similar results were observed by Myari et al23 in the bis-heteroleptic complex attached with a short amino acids sequence [Ru(bpy) 2 (m-bpy-GHK)]Cl 2 (GHK = glycine-L-histidine-L-lysine, m-bpy = 4-methyl-2,2′-bipyridine), where the degeneracy in 1 H chemical shifts of the two bpy ligands was detected. The CIS of dppz is 1.38 and 1.42 ppm at positions 2 and 11, respectively, while 0.82 and 0.99 ppm for Me 2 phen at 2 and 11, and 0.76 and 1.07 ppm for A2 and A11, respectively.…”
Section: Resultssupporting
confidence: 88%
“…Inspection of Figure 9a reveals that the degeneracy in chemical shifts due to the C 2V symmetry of ligand B (dppz) remains unchanged in rac–1a (except for a 0.04 ppm difference between positions 2 and 11), which suggests the very similar anisotropic effect of the substituted phenanthrolines in this arrangement. Similar results were observed by Myari et al23 in the bis-heteroleptic complex attached with a short amino acids sequence [Ru(bpy) 2 (m-bpy-GHK)]Cl 2 (GHK = glycine-L-histidine-L-lysine, m-bpy = 4-methyl-2,2′-bipyridine), where the degeneracy in 1 H chemical shifts of the two bpy ligands was detected. The CIS of dppz is 1.38 and 1.42 ppm at positions 2 and 11, respectively, while 0.82 and 0.99 ppm for Me 2 phen at 2 and 11, and 0.76 and 1.07 ppm for A2 and A11, respectively.…”
Section: Resultssupporting
confidence: 88%
“…A number of groups have attached single amino acids and short peptides to transition metal complexes [73][74][75][76][77][78][79][80][81][82][83]. Recently, Karidi et al reported the first example of an amino acid chain attached to a chloro(polypyridyl) ruthenium(II) complex [84].…”
Section: Octahedral Metallointercalatorsmentioning
confidence: 99%
“…Among the most studied compounds is the complex [Ru(bpy) 3 ] 2+ , which shows a weak association with DNA, most probably due to the electrostatic interactions with the DNA phosphates [12][13][14]. Attempts to undertake the random binding of ruthenium tris-chelates to DNA have been raised by tethering a DNA-recognition peptide to one of the bipyridine ligands [15][16][17][18][19][20][21][22][23]. It has been suggested that the nature of the peptide affects the DNA binding affinity of the ruthenium complex [15,17,18].…”
Section: Introductionmentioning
confidence: 99%